KEBIJAKAN PERENCANAAN URBAN RAILWAY YOGYAKARTA - MAGELANG - , NIKEN SITALAKSMI WIDJAJA; , Prof. Ir. Sigit Priyanto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
because Yogyakarta-Magelang are student cities and tourist destinations in Central Java, Indonesia. Both cities have intensity mobility of transportation activities that cause air pollution impact. Geographic and population growth need the improved transportation. Meanwhile, it is difficult to expand the road network, of high prices of the existing limited land. In order to anticipate the increasing movement in the future with increasing economic activity in both regions, an alternative transportation mode (railway) is needed to improve the efficiency, so that the traffic problems (congestion, accidents, air pollution) can be reduced. The urban railway Yogyakarta-Magelang expected to be the right solution in dealing with traffic issues. Planning policy of urban railway Yogyakarta-Magelang must consider the interest of each of components involved and the various criteria of service. The technique of determining the respondents used in this study is cluster sampling (respondent group). While the type and number of respondents who selected is determined by purposive sampling (selected respondents). Based on the analysis of interest rate of the component with the method of Analytical Hierarchy Process (AHP) found that components that have the greatest interest in the determination of planning policy urban railway Yogyakarta- Magelang are: (i) user 56%, (ii) government 19%, (iii) operator 15%, and (iv) transport expert 10%. The results of the analysis is based on priority criteria indicate that the interest component of the most influential criteria in planning policy of urban railway Yogyakarta-Magelang is convenience and safety. While smallest influential criteria is the ease of service. The results of this study is expected to be used Government / all parties whom it may concern with the planning of urban railway Yogyakarta-Magelang in any decision-making.